Management of swallowing and communication difficulties in Down syndrome: A survey of speech-language pathologists. (2nd January 2017) - Meyer, Carly; Theodoros, Deborah; Hickson, Louise
Abstract: Purpose: To explore speech pathology services for people with Down syndrome across the lifespan. Method : Speech-language pathologists (SLPs) working in Australia were invited to complete an online survey, which enquired about the speech pathology services they had provided to client/s with Down syndrome in the past 12 months. The data were analysed using descriptive statistics. Result: A total of 390 SLPs completed the survey; 62% reported seeing a client with Down syndrome in the past 12 months. Most commonly, SLPs provided assessment and individual intervention for communication with varying levels of family involvement. The areas of dysphagia and/or communication addressed by SLPs, or in need of more services differed according to the age of the person with Down syndrome. SLPs reported a number of reasons why services were restricted. Conclusion: There is a need to re-assess the way that SLPs currently provide services to people with Down syndrome. More research is needed to develop and evaluate treatment approaches that can be used to better address the needs of this population.